Language, Task and Situation: Authenticity in the Classroom - Ken Beatty (National Research University Higher School of Economics, 2015)
There is debate on the use of authenticity in language classrooms in terms of language, task, and situation. "Authenticity of language" spans a continuum that begins with inauthentic materials - wholly created by a teacher or materials developer - to constructed materials, modified from real-world materials, to those materials created for non-pedagogical L1 purposes. "Authenticity of task" questions whether students are engaging with language materials in a way that would appear natural outside the classroom. "Authenticity of situation" refers to non-classroom contexts. Complicating ideas of authenticity is the question of materials selection. This paper explores teachers' awareness of authenticity and suggests ways to incorporate authentic language, tasks, and situations to enhance classroom learning.